Preclinical evaluation of the BET bromodomain inhibitor BAY 1238097 for the treatment of lymphoma. (27th June 2017) - Bernasconi, Elena; Gaudio, Eugenio; Lejeune, Pascale; Tarantelli, Chiara; Cascione, Luciano; Kwee, Ivo; Spriano, Filippo; Rinaldi, Andrea; Mensah, Afua A.; Chung, Elaine; Stathis, Anastasios; Siegel, Stephan; et al.
Summary: The epigenome is often deregulated in cancer and treatment with inhibitors of bromodomain and extra‐terminal proteins, the readers of epigenetic acetylation marks, represents a novel therapeutic approach. Here, we have characterized the anti‐tumour activity of the novel bromodomain and extra‐terminal (BET) inhibitor BAY 1238097 in preclinical lymphoma models. BAY 1238097 showed anti‐proliferative activity in a large panel of lymphoma‐derived cell lines, with a median 50% inhibitory concentration between 70 and 208 nmol/l. The compound showed strong anti‐tumour efficacy in vivo as a single agent in two diffuse large B cell lymphoma models. Gene expression profiling showed BAY 1238097 targeted the NFKB/TLR/JAK/STAT signalling pathways, MYC and E2F1‐regulated genes, cell cycle regulation and chromatin structure. The gene expression profiling signatures also highly overlapped with the signatures obtained with other BET Bromodomain inhibitors and partially overlapped with HDAC‐inhibitors, mTOR inhibitors and demethylating agents. Notably, BAY 1238097 presented in vitro synergism with EZH2, mTOR and BTK inhibitors. In conclusion, the BET inhibitor BAY 1238097 presented promising anti‐lymphoma preclinical activity in vitro and in vivo, mediated by the interference with biological processes driving the lymphoma cells. Our data also indicate the use of combination schemes targeting EZH2, mTOR and BTK alongside BET bromodomains.